2021
DOI: 10.1002/job.2500
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking and closing the gender gap in creative performance: A multilevel model

Abstract: Summary Building upon and extending the interactionist perspective of creativity, social role theory, and role congruity theory, we develop an integrated multilevel model to examine gender differences in creative self‐efficacy and determine how the contextual factor of team psychological safety shapes employees' creative self‐efficacy and, through this motivational mechanism, influences their creative performance. Using data from a sample of 335 employees from a large food manufacturer collected over three tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 129 publications
(230 reference statements)
1
22
0
1
Order By: Relevance
“…Therefore, to resolve this challenge, steps must be taken to ensure women believe that their creative efforts are as situationally appropriate as those of their male counterparts. Psychologically safe work climates have emerged as one method by which this can be accomplished (Hora et al, 2021), and our research similarly showed that cultures that value communion featuring civility and concern for others may serve to reduce the gender gap.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Therefore, to resolve this challenge, steps must be taken to ensure women believe that their creative efforts are as situationally appropriate as those of their male counterparts. Psychologically safe work climates have emerged as one method by which this can be accomplished (Hora et al, 2021), and our research similarly showed that cultures that value communion featuring civility and concern for others may serve to reduce the gender gap.…”
Section: Discussionsupporting
confidence: 60%
“…Put differently, the internalization of gender stereotypes could curb women's self-confidence and motivation to invest in creative endeavors, affording fewer opportunities to excel. Consistent with this theorizing, despite exhibiting similar creative abilities, past work has shown that women possess lower creative self-efficacy (Hora et al, 2021) and diminished "self-expectations for creativity" (Carmeli & Schaubroeck, 2007). Altogether, women's internalization of gendered roles and expectations may limit their expectancy and effort to engage in creative performance, regardless of their creative ability.…”
Section: The Gender Difference In Creative Performancementioning
confidence: 59%
See 2 more Smart Citations
“…The Creative Self-efficacy Scale ( Tierney and Farmer, 2002 ) was used to measure creativity in FL learners with four items (e.g., “I have confidence in my ability to solve problems creatively”). This scale has been used in various fields including business, economics, and education ( Gong et al, 2009 ; Puente-Díaz, 2016 ; Hora et al, 2021 ) and has shown good psychometric properties in different countries ( Liu et al, 2017 ; Alvarez-Huerta et al, 2021 ). This scale can measure the following three aspects of FLL students: (i) whether they have confidence in overcoming difficulties encountered in the process of FLL by finding innovative methods; (ii) whether they are conscious of absorbing the good learning experiences of others so as to create their own FLL approaches; and (iii) whether they can constantly come up with new ways to meet the challenges in FLL.…”
Section: Methodsmentioning
confidence: 99%